Concurrent Validity of the Bayley-III and the Peabody Developmental Motor Scales-2 at 18 Months. (3rd September 2019) - Gill, Kamaldeep; Osiovich, Alan; Synnes, Anne; A. Agnew, Jennifer; Grunau, Ruth E.; Miller, Steven P.; Zwicker, Jill G.
Abstract: Aim: To determine concurrent validity between the Bayley Scales of Infant and Toddler Development, 3 rd edition (Bayley-III) and the Peabody Developmental Motor Scales, 2 nd edition (PDMS-2). Methods: Both assessments were administered to 184 preterm children at 18 months corrected age; standard scores for total score, gross motor, and fine motor were calculated for each child. Cross-tabulation and Pearson correlation coefficient (r) determined concurrent validity between the Bayley-III and the PDMS-2 motor domains. Results: High correlations were found between total motor ( r  = 0.88), gross motor ( r  = 0.88), and fine motor scores ( r  = 0.79). Both assessments had 93% agreement on classification for motor impairment; 23 children were identified by both assessments as having motor impairments, but 12 children were identified differently on each assessment (7 as impaired on PDMS-2 but average on Bayley-III; 5 as impaired on Bayley-III but average on PDMS-2). Most children with motor impairments were identified as 1SD below the mean on the PDMS-2 (27/30) and Bayley-III (18/28); however, the Bayley-III identified more children 2SD below the mean (10/28) compared to the PDMS-2 (3/30). Conclusions: Both the Bayley-III and PDMS-2 identify motor delays in children; however, clinicians should be aware of the concurrent validity as each assessment may lead to differing results.